Mathematical simulation of railway track and trackside contamination with silt - V. M. Belkov; M. A. Zhuravlyova (Вестник Научно-исследовательского института железнодорожного транспорта)
Railway track and trackside contamination with mineral particles results from transboundary transfer of emissions from industrial facilities, which are deposited on the surface of crushed stone prism and the wayside soil band. Transportation of ores suggests partial entrainment of dust particles from the top granular layer 10 - 15 cm thick; electrified lines add dust-like particles of copper contact wires, which turn to a fixed form as hydroxides. Concentration of mobile forms of metal ores in the wayside soil band is significantly less than maximum allowable concentrations (MACs). To measure gross concentration of metal hydroxides in soils by atomic absorption method is an expensive and time-consuming procedure including withdrawal and preparation of large numbers of samples. To expedite the process and to reduce the costs of measuring the contamination of crushed stone prisms and track waysides with heavy metals we need to get the concentration dependence formula allowing to obtain the full pollution curve for the wayside and adjacent zone from one or two samples depending on the coordinates from the rail head and to determine the background concentration. Simulation of a flow around a complex shape object in turbulent conditions relates to the most difficult tasks in fluid dynamics. To describe the turbulent motions in layered gaseous environment we normally use the instruments common for the theory of fluctuations and the theory of mass transfer - like the second Fick’s equation, from which we can find the required functions of the concentration of harmful substances, depending on the vertical Z and the horizontal X coordinates. To expedite the process and to reduce the costs of measuring the contamination of the track wayside a simulation model for turbulent areas was developed on the grounds of fluctuation theory; depending on the coordinates from the rail head, one sample allows to obtain the full pollution curve for the wayside. Comparison of theoretical and experimental curves has shown a satisfactory match.